The Role Of Teachers In Implementing Curriculum 13 In Primary Schools - Alek, Rendi; Fitria, Happy; Eddy, Syaiful (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to determine : 1) how the role of teachers in the implementation of the 2013 curriculum , 2) what are the determinants of the 2013 curriculum implementation , 3) the implementation of the 2013 curriculum can optimize the role of teachers . The results showed that the role of teachers at SD Negeri 1 Rantau Sialang in implementing the 2013 curriculum, namely teachers as implementers , teachers as adapters , teachers as curriculum developers and teachers as curriculum researchers. The teacher is not only the implementer of the curriculum, but also as the alignment of the curriculum with the characteristics and needs of students and regional needs. The supporting factors in the implementation of the 2013 Curriculum at SD Negeri 1 Rantau Sialang include the availability of facilities and infrastructure such as syllabus, lesson plans, teacher handbooks and student textbooks. Inhibiting factor, namely the unpreparedness of the 2013 Curriculum. This is because there are still many obstacles and obstacles. However, SD Negeri 1 Rantau Sialang itself is ready or not ready to implement the 2013 Curriculum in compliance with the orders of the Ministry of Education and Culture. Implementation of the 2013 Curriculum can optimize the role of teachers in SD Negeri 1 Rantau Sialang . This is the use of methods in learning that must be adapted to the material to be taught and the conditions of the students themselves when participating in the teaching and learning process.